Prerequisites for the development of the concept of health-forming technologies in the process of adaptive physical education of school-age children with hearing impairment - Kashuba, Vitaliy; Maslova, Olena (Journal of Education, Health and Sport, 2018)
Prerequisites for the development of the concept of health-forming technologies in the process of adaptive physical education of school-age children with hearing impairment Prerequisites for the development of the concept of health-forming technologies in the process of adaptive physical education of school-age children with hearing impairment National University of Physical Education and Sports of Ukraine, Kyiv. Actuality. The leading position of the contemporary issues of health-forming activity of children and youth presented in the form of a methodological basis for the formation of a positive motivation for a healthy lifestyle of the younger generation, especially with specific disabilities in the state of health, separates the central component of this process from the humanistic approach, the essence of which is creating a favorable situation for the readiness of the present youth to perceive and adequately respond to the educational activities of the school and social environment that are implemented in the process of their physical education. Objectives of the study: determination of priority directions of optimization of the process of physical education of students with hearing impairments, selection of rational means and methods that fully satisfy the specific needs of this contingent based on the study of their interests not only during physical education, but also correctional activities, self-organized motor activity Research results. The data obtained during the study showed that most children with hearing impairments understood the problems of their own health and had a desire to carry out activities aimed at improving their level, defining for themselves as the main criterion the physical state of their organism. The results of the questionnaire survey of 236 schoolchildren aged 13 to 19 years with different established hearing disorders supplemented the systematization of preconditions and scientifically substantiated the necessity of developing the concept of health-forming technologies in the process of adaptive physical education of children of school age with hearing impairments. Conclusions. The generalization of the research results substantiates the necessity of developing innovative technologies for optimizing the process of physical education of children with hearing impairments and may be represented by the following recommendations: the preconditions of this process should be based on objective results of comprehensive and comprehensive research; the central component must take into account the needs and peculiarities of the manifestation of the motivational sphere of this contingent.